A Conversation with Nancy Baym, Author of Playing to the Crowd. (April 2020) - Lingel, Jessa
How has digital technology changed the relationship between musicians and their fans? What can the experiences of performers teach the rest of us about technology, self-promotion, and community? This bookcast describes key themes from Playing to the Crowd, discusses the methods behind the book, and addresses theoretical frameworks.